The Determinants Of Corporate Social Disclosure In The Annual Reports Of Malaysian Construction Companies: An Application Of Stakeholder Theory - Gembri, Abdulmunaem .S. M. (2013)
This study seeks to investigate the motivations that make the Malaysian construction publicly listed companies voluntarily provide social and environmental information in their annual reports. The first objective of this research is to examine the level of corporate social disclosures present in 2010 Malaysian construction listed companies’ annual reports. The second objective, is the application of Ullmann’s (1985) stakeholder framework, which contains three dimensions namely stakeholder power; strategic posture; and economic performance, to determine their ability to explain why these companies disclose voluntarily social and environmental information in their annual reports. Companies without a 2010 annual reports are omitted from the construction companies listed on the Bursa Malaysia to create a sample of 107 companies. Data was collected to measure components of corporate social disclosure, and proxies for Ullmann’s three-dimensional stakeholder framework were applied. This study examines the level of corporate social disclosures in relation to creditor stakeholder power represented by return on equity; investors’ stakeholder power represented by government shareholders and foreign shareholders and employee stakeholder power represented by employee share ownership. Evidence shows that both creditor and government shareholders (measures investor power), and employee share ownership does empower stakeholder pressure regarding the quantity and quality of corporate social disclosures. In contrast, foreign shareholders were an insignificant proxy and did not serve in explaining the level of corporate social disclosure in the companies’ annual report. The results also find that companies displaying a more active strategic posture towards social and environmental issues disclose higher quantity and quality of corporate social disclosure information than companies displaying a less active posture to these issues. Companies employ strong corporate governance mechanisms to, strategically, manage their relationship with their stakeholders through disclosing voluntary social and environmental information. The presence of corporate social responsibility committee in the companies’ board structure is also evidence of strategic posture, but only in quantity of corporate social disclosure. Companies with higher economic performance disclose a greater amount of corporate social disclosure information than, companies with lower economic performance. Economic performance represented by average return on assets. The results showed that larger companies are significantly associated with higher levels of corporate social disclosures.